Estudio de prefactibilidad para la instalación de una planta productora de vodka a partir de papas nativas - Montero Sandoval, Francis Carlos (2020)
The present study seeks to determine the feasibility of installing a vodka production plant from native potatoes. The idea of the project arose due to the development of the industry of this alcoholic beverage in Peru, with the incorporation of new Premium vodka production plants. Likewise, it is currently seeking to boost national production and the variety of inputs that Peru offers, so using native potatoes makes it a potentially attractive product both in the country and in the global market. First, in Chapter 1 the research problem to be addressed and the questions generated from it will be detailed. Likewise, both general and specific objectives, the hypothesis and the scope of this project were established. Likewise, in Chapter 2 the research works used to obtain information were identified in the referential framework and the necessary terms for understanding the work were defined in the conceptual framework. Second, in chapter 3 the product was defined, the external analysis was carried out through Porter's 5 forces, and the Canvas Model was implemented to shape the business idea. In addition, the project demand was determined through the projection of the historical demand, the segmentation and the study carried out through the survey. Likewise, the offer in Peru was analyzed and the strategy to be followed for the development of the project was established. Having defined the product, Chapter 4 proceeded to carry out a study of macro and micro location of the plant, considering factors that facilitate the development of plant operations, resulting in the department of Ayacucho and the province of Huamanga. The project will thus develop the economy of the area and generate a positive impact on employment. The project investment amounts to 1,799,097 soles with a 3-year payback period and an added value of 3.2 million soles. Although the initial sales price is very close to the cost of sales, the net margin increases over the years of the project.